Trouble in Market Paradise: Development of the Regional Transmission Operator. Issue 2 (2nd April 2016) - Rose, Kenneth
Abstract: Regional transmission organizations (RTOs) have evolved from "power pool" arrangements between utilities to complex organizations that operate a region's transmission system and power markets. These RTOs are administered with only peripheral public input. This paper reflects on how RTOs, as a result, have developed very complex market structures that few can or do understand. An RTO's capacity construct is used to illustrate the point of this complexity and ad hoc nature. The paper also discusses reforms that are needed to align the RTOs behavior with Harry M. Trebing's public interest regulatory philosophy.